PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING SULAMAN SMOCK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI SMKN 1 SOOKO MOJOKERTO - Pratesya, Nevi Jutalim; Rahayu, Imami Arum Tri; Nashikhah, Ma’rifatun; Mayasari, Peppy (Jurnal Socia Akademika, 2023)
The purpose of this study is to determine the effect of applying the project learning model. Based learning on student activities on the basic competencies of making smock embroidery. The type of research is Classroom Action Research. The data collection method in this study uses observation methods to determine the implementation of the project learning process Based on learning, then use response questionnaires to determine student responses to Project Based Learning Learning Model, and Test Method to Determine Learning Outcomes Students after the implementation of the Project Based Learning learning model embroidered smock. The results of the research state that the project-based learning model for smock embroidery can be seen with final results of 94% for teacher activity and 93% for student activity which are stated to be very good. In the response questionnaire, the percentage of students who got 78.9% was included in the good category. Student learning outcomes were declared complete in the KKM with the percentage of students who completed it being 100% in cycle III in both the cognitive and psychomotor domains. The results of this research show Students using the project-based learning model in smock embroidery can improve student learning outcomes so after this research, researchers hope that teachers can apply this learning model to the subject of clothing decoration.